Health, Disease and Healing in Medieval Culture
XXIV, 204 p.
Keywords: This volume of studies seeks an anthropological view of medicine and the healing arts as they were situated within the lives of medieval people. Miracle cures and charms as well as drugs and surgery fall within the scope of the authors represented here, as does advice about diet and regimen. As well, the volume looks at wellness and illness in broad contexts, avoiding the tendency of modern medicine to focus on the isolation and definition of pathological states.